PCR detection of Neospora caninum, Toxoplasma gondii and Encephalitozoon cuniculi in brains of wild carnivores - Hůrková, Lada; Modrý, David (Veterinary parasitology, 2006)
Neospora caninum, Toxoplasma gondii and Encephalitozoon cuniculi are important pathogens with affinity to the central nervous system of many animals. 240 brains of wild carnivores were examined by PCR-based diagnosis. The presence of N. caninum DNA was confirmed in 4.61% (7/152) red foxes (Vulpes vulpes). DNA of T. gondii was found in 4.92% (3/61) martens (Martes sp.) and in 1.32% (2/152) red foxes. DNA of E. cuniculi was determined in 3.28% (2/61) martens and in one examined European otter (Lutra lutra). There were no co-infections found. These results provide the first evidence of E. cuniculi in the European otter, the first report of N. caninum in foxes in the Czech Republic and confirm the presence of T. gondii in wild carnivores in the Czech Republic.
Keywords: protozoální DNA; encephalitozoonóza; Toxoplasma; polymerázová řetězová reakce; DNA, Fungal; kokcidióza; Brain; Česká republika; Animals, Wild; prevalence; divoká zvířata; DNA, Protozoan; Coccidiosis; DNA fungální; Czech Republic; Neospora; Toxoplasmosis, Animal; Animals; Encephalitozoon cuniculi; zvířata; Prevalence; mozek; Financing, Organized; Polymerase Chain Reaction; Carnivora; Encephalitozoonosis; financování organizované; toxoplazmóza zvířat